Request for postponing the deduction program against L/C remaining unadjusted amount - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding request for postponing the deduction program against L/C remaining unadjusted amount of BRAC University new campus project.